Comparative analysis of buildings with armed concrete structural systems: “Duales versus Diagrid”. - Núñez Herrera, José Luis (2019)
In order to investigate the seismic behavior of the concrete Diagrid structures, 03 models of 06-level buildings are proposed with a typical 30 m x 37.5 m plant located in an area of high seismicity in Peru. A comparative analysis has been made between two structural systems on the one hand the conventional or orthogonal system and on the other the Diagrid system of reinforced concrete, for the latter two types or models that we will call type A and type B, whose modulation will be analyzed, will be analyzed. every 02 and 04 floors respectively. The three models will have the same characteristics; roofed area, dimensions in plan and elevation, construction materials and loading loads, geographical location, soil type, use and importance, Basic Coefficient of Reduction of the Seismic Force (Ro), these characteristics generate the factors that are regulated by E.030.2016 that defines the procedure for seismic analysis. In this research it has been shown that of the buildings studied (03 models) those with the structural Diagrid system of reinforced concrete (Diagrid type A and Diagrid type B) are more efficient than the conventional system (frames with structural walls), weight of the structure results in lower costs and lower demands of foundation structures of the three models, the lightest is the Diagrid type B system, both Diagrid systems are 30% lighter than the conventional system, the amount of steel needed to the diagonals of the Diagrid type A systems is 29% less than the longitudinal steel required for the structural walls of the conventional system, while Diagrid type B, requires 40% less than the conventional system.